Faith and Enterprise: The Leadership of Kyai in Driving Islamic Entrepreneurship - Sopiyah (Tadibia Islamika: Journal of Holistic Islamic Education, 2025)
Leadership roles serve as a critical lens for examining program implementation within Islamic boarding schools (pesantren), particularly through the perspectives of key stakeholders including leaders, administrators, and students. This study investigates the leadership role of KH. Tatang Astarudin in implementing entrepreneurship programs at his institution. Drawing on Henry Mintzberg's theoretical framework, leadership roles are categorized into three dimensions: First, interpersonal roles encompassing figurehead, leader, and liaison functions. Second, informational roles including monitor, disseminator, and spokesperson responsibilities. Third, decisional roles comprising entrepreneur, disturbance handler, and negotiator capacities. The research findings at Pondok Pesantren Mahasiswa Universal demonstrate that KH. Tatang Astarudin effectively fulfills all aspects of Mintzberg's leadership role theory. In his interpersonal capacity, he successfully serves as an exemplary figure for both students and teaching staff. Regarding his informational role, he adeptly manages communications with external parties while maintaining institutional integrity. In his decisional capacity, he exhibits strong entrepreneurial initiative by generating innovative ideas that have significantly advanced the institution's entrepreneurship programs. Furthermore, he demonstrates competence in problem-solving and establishing productive partnerships with external organizations, thereby creating sustainable pathways for institutional development and student entrepreneurial growth.